Characterization of defatted pili (Canarium ovatum Engl.) pulp flour - Acompañado, Mary Julienne R.; Palomeno, Antonio (Quezon City University of the Philippines Diliman, 2025)
In this study, the proximate composition, physicochemical, functional, and morphological properties of defatted pili pulp flour were investigated. The flour defatted using maceration coupled with manual pressing (DPPF 2) was selected for further characterization due to its significantly (p-value < 0.05) lower crude fat content compared to that of the full-fat flour (FPPF) and flour defatted using manual pressing method (DPPF 1). The results of the proximate analysis (% dry basis) revealed that DPPF 2 contained high amounts of crude fat (24.83%), crude fiber (21.00%), and ash (3.67%), but low levels of moisture (1.77%), crude protein (6.09%), total carbohydrates (7.43%), and nitrogen-free extract (44.41%). Its energy value was determined to be 278 kcal/100 g. Characterization of its physicochemical properties indicated a mean pH of 5.37 and water activity of 0.432, with color properties reflecting its dark brown color. Its bulk (0.36 g/mL) and tapped (0.54 g/ml) densities and flowability suggested that it has high cohesiveness and fair flow character. Analysis of its functional properties showed high least gelation concentration (14%), solubility (33.44 g/100 g), swelling capacity (664.16%), oil absorption capacity (139.09%), and water absorption capacity (363.29%), which emphasized its potential as infant food ingredient, flavor carrier, humectant, bulking agent and thickener. Lastly, its morphological properties suggested a heterogeneous morphology with an average particle size of 93.90 μm. Overall, this study indicated that defatted pili pulp flour holds significant potential for various food formulations due to its nutritional viability, though some of its properties may require further refinement to enhance its functionality.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Food industry and trade; Flour mills -- Phiippines; Functional properties; Morphological properties; Defatted pili pulp flour; Physicochemical properties; Pili nut